Distribution of BCR::ABL1 Transcript Types and Response to Therapy in Pediatric Patients with Chronic Myeloid Leukemia - Seiser, Esra; Behrens, Yvonne L.; Lukat, Sabine; Sembill, Stephanie; Karow, Axel; Suttorp, Meinolf; Metzler, Markus; Krumbholz, Manuela (Journal of Molecular Diagnostics, 2025)
Achieving a stable deep molecular response with the option to discontinue tyrosine kinase inhibitor treatment is the new therapeutic goal for patients with chronic myeloid leukemia (CML). Several studies have shown that individuals expressing the BCR::ABL1 e14a2 transcript achieve a major molecular response more rapidly than those with the e13a2 transcript. However, technical issues may have confounded these observations, and data for pediatric patients are limited. This study analyzed the distribution of BCR::ABL1 transcript types and their association with baseline hematologic parameters and tyrosine kinase inhibitor treatment response in 102 pediatric patients with CML. Subgroups were compared on the basis of results from routine multiplex PCR and droplet digital PCR (ddPCR). The dynamics of the transcript types under therapy were evaluated in detail in patients and a CML cell line co-expressing e13a2 + e14a2. ddPCR has identified significantly more patients co-expressing e13a2 + e14a2 than classified on the basis of routine diagnostics. This has implications for the categorization of individual subgroups. Comparing transcript dynamics in individuals or a cell line expressing both variants simultaneously revealed no differences in treatment response. When analyzing clinical data based on the transcript classification of patients, it is important to use methods that detect both variants with equal sensitivity. In ddPCR, the transcript variants' ratio is accurately shown because there is no competitive template amplification, as seen in multiplex and quantitative real-time PCR.
CRIS-Team Scopus Importer:2025-02-28